Training in HSS Learning Coding Platform to Enhance Students' Competence in Web Design - Denny Sagita Rusdianto; Issa Arwani; Fajar Pradana; Faizatul Amalia (Universitas Lambung Mangkurat, 2024)
Website training is becoming increasingly important for students in today's digital era. This is due to the growing use of the internet as a source of information and communication. Website training can help students develop the information technology skills needed in various aspects of life, including education and careers. Additionally, website training can help students broaden their horizons and enhance their creativity in creating digital content. Thus, students will be better prepared to face future challenges that increasingly rely on information technology. The training method provided to students in this community service project uses service learning. The website training is structured in schools or through community service programs involving 32 vocational high school students in Malang City. The HSS Learning Coding Platform Training was conducted as a gamification-based learning medium through this community service activity. Both platforms, namely W3Schools and the Gamification Application, have proven effective based on tests given to improve students' understanding of HTML. This is evidenced by the increase in median scores from the pre-test to the post-test. Website training helps students develop essential digital skills and positively contributes to their future careers and lives.